Partial Inverse Spectral Problem for the Sturm-Liouville Operator With Delay - Pikula, Milenko; Nedić, Dragana; Čatrnja, Elmir (Sarajevo Journal of Mathematics, 2022)
In this paper we study an inverse spectral boundary value problem for second-order differential equations on a finite interval with delay. For given conditions, we find the expression for the asymptotics of the eigenvalues of the posted problem. Then we examine the inverse problem and by using two sequences of eigenvalues obtained by varying the boundary condition at the right end, we construct the operator and prove its uniqueness.